Systemic effects of epidural steroid injections for spinal stenosis. Issue 5 (May 2018) - Friedly, Janna L.; Comstock, Bryan A.; Heagerty, Patrick J.; Bauer, Zoya; Rothman, Micol S.; Suri, Pradeep; Hansen, Ryan; Avins, Andrew L.; Nedeljkovic, Srdjan S.; Nerenz, David R.; Akuthota, Venu; Jarvik, Jeffrey G.
Abstract : Abstract: This analysis of the lumbar epidural steroid injections for spinal stenosis multicenter randomized controlled trial data identifies the degree of and risk factors for cortisol suppression after epidural steroid injections in older adults with spinal stenosis. Four hundred patients aged 50 years and older with back or leg pain and central lumbar spinal stenosis completed baseline demographic and psychosocial measures. Morning serum cortisol levels were measured at baseline and 3 weeks after initial injection. Patients were randomized to receive epidural injections of either local anesthetic with corticosteroid (n = 200) or local anesthetic only (n = 200). The specific corticosteroid was chosen at the treating physician's discretion (methylprednisolone, betamethasone, triamcinolone, or dexamethasone). Thirty-two patients (20.3%) treated with corticosteroid experienced cortisol reduction at 3 weeks of >50% compared with 10 patients (6.7%) treated with lidocaine only (adjusted treatment effect = 3.5, 95% confidence interval: 1.6-7.9, P = 0.002). The effect on 3-week cortisol changes did not differ by demographic or patient-level characteristics. Those treated with methylprednisolone or triamcinolone had an average 3-week cortisol reduction of 41.0% ( P = 0.005) and 41.6% ( P < 0.001) from baseline, respectively, whereas patients treated with betamethasone or dexamethasone were not significantly different than comparable patients in the lidocaine arm. The higher rates of cortisol suppression at 3 weeks in those receiving epidural corticosteroid injections, particularly with longer-acting insoluble corticosteroid formulations, are consistent with sustained systemic absorption of corticosteroid. Abstract : In older adults with spinal stenosis, significantly higher cortisol suppression occurred at 3 weeks in those randomized to receive epidural corticosteroid injections vs lidocaine alone.